Affiliation motive and social interactions in people’s daily life: a temporal processes approach using ecological momentary assessment and mobile sensing - Wrzus, Cornelia; Roos, Yannick; Krämer, Michael D.; Schoedel, Ramona; Back, Mitja D.; Richter, David (Journal of personality and social psychology, 2025)
Individual differences in social traits such as the affiliation motive are closely linked to the formation and maintenance of social relationships. Most previous research focused on long-term characteristics or momentary assessments of social relationships (e.g., social network size, relationship quality), whereas theoretical accounts have emphasized the temporal dynamics, that is, how social interactions unfold over time. The present studies examined how social interactions unfold within days as well as between days, taking personality traits and situational affordances into account. In two multimethod studies (Study 1: N = 307, age 18-80 years, 51% female; Study 2: N = 385, age 19-84 years, 48% female), we assessed participants’ social interactions in daily life using ecological momentary assessments and mobile sensing over 2 and 14 days, respectively. Furthermore, participants answered questionnaires on affiliation, additional social traits, and situational affordances, for example, the voluntariness of social situations. Multilevel lead-lag analyses showed that affiliation predicted momentary social desires but not future social interactions, except when social interactions were assessed with unobtrusive mobile sensing. Situational affordances, such as the valence and voluntariness of social interactions, additionally predicted social desires and future contact. The results were largely specific to affiliation and not observed for extraversion. Future research on social interactions would benefit from (a) examining and specifying meaningful timescales of social relationship processes, (b) following the renewed interactionist call for considering person and situation factors, and (c) integrating the myriad of social trait concepts in theories and measurements.
Gesehen am 04.11.2025